The phonology of consonants - Bennett, Wm G (Cambridge University, 2015)
Includes bibliographical references and indexes; Machine generated contents note: 1. Introduction; 2. The surface correspondence theory; 3. Kinyarwanda: the effects of domain edges, and the adequacy of a single SCorr relation; 4. Sundanese: complementary assimilation and dissimilation; 5. Quechua and Obolo: the role of syllable edges; 6. Chol and Ponapean: complete identity effects; 7. Zulu labial dissimilation: SCTD and the OCP; 8. Segmental blocking effects in dissimilation; 9. Typological survey of dissimilation; 10. Concluding remarks